Power and exclusions in Health Sciences training. Suggestions for improvement in patient care from complementarity - David Conde Caballero (Universidad de Alicante, 2015)
Introduction: The importance of the health-disease-care is a universal fact executed through different models. West proposes the Biomedical model, whose achievements are limited by the exclusion that makes the socio-cultural variables of the sick. Objective: A reflection on the possibilities for improvement to enable a close to holism decisive assistance, not only for greater professionalism but also the formation of a real nurse identity, is the main objective. Methodology: To try to give, long referenced in the field of medical anthropology we venture robust response to the reading of two classics from the likes of Foucault and Gramsci, allowing us to suggest a line in the search for reasons and solutions on the problems surrounds us. Development: A reasonable way is looming on the contribution that complementary forms of care possible. In this sense, the current nursing should seek a return to its ethos of care, thus moving away from deterministic rules that have condemned the subaltern. Conclusions: A change in training patterns are established as key feature to determine real improvement in processes of care and allow the basic right to quality care.